2016
DOI: 10.1371/journal.pone.0163175
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Detection and Simultaneous Discrimination of Influenza A and B Viruses in Nasopharyngeal Swabs in a Single Assay Using Next-Generation Sequencing-Based Diagnostics

Abstract: Reassortment of 2009 (H1N1) pandemic influenza virus (pdH1N1) with other strains may produce more virulent and pathogenic forms, detection and their rapid characterization is critical. In this study, we reported a “one-size-fits-all” approach using a next-generation sequencing (NGS) detection platform to extensively identify influenza viral genomes for diagnosis and determination of novel virulence and drug resistance markers. A de novo module and other bioinformatics tools were used to generate contiguous seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 46 publications
1
25
1
Order By: Relevance
“…Due to multiple limitations including reliable access to specific pathogen-free ECEs in other countries, increasing importation costs, and regulatory restrictions that prevent rapid sample evaluation, we sought to improve virus characterization by performing NGS directly from swab samples. Although NGS has been previously used to characterize IAV from original samples (Ren et al, 2013;Seong et al, 2016;Wang et al, 2008;Zhao et al, 2016), such studies were not aimed at comparing it to viral isolation or determining whether it could result in different consensus sequences. Using swabs collected from wild birds in Guatemala during the 2013-2014 season, we amplified and obtained sequence information by swab-NGS from 29 out of 74 IAV rRT-PCR-positive samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to multiple limitations including reliable access to specific pathogen-free ECEs in other countries, increasing importation costs, and regulatory restrictions that prevent rapid sample evaluation, we sought to improve virus characterization by performing NGS directly from swab samples. Although NGS has been previously used to characterize IAV from original samples (Ren et al, 2013;Seong et al, 2016;Wang et al, 2008;Zhao et al, 2016), such studies were not aimed at comparing it to viral isolation or determining whether it could result in different consensus sequences. Using swabs collected from wild birds in Guatemala during the 2013-2014 season, we amplified and obtained sequence information by swab-NGS from 29 out of 74 IAV rRT-PCR-positive samples.…”
Section: Discussionmentioning
confidence: 99%
“…The utility of next-generation sequencing (NGS) and the ability to sequence directly from the original swab material for rapid IAV detection will produce more complete and accurate data reflective of naturally occurring subtypes and genetic diversity (McGinnis, Laplante, Shudt, & George, 2016;Zhao et al, 2016). In the present report, we show how performing NGS from original swab (swab-NGS) material can improve IAV characterization from field samples.…”
mentioning
confidence: 88%
“…The additional benefit of sequencing over virus isolation is that the sequences would be useful for analyzing the influenza virus outbreak clusters [338], virus evolution or reassortment [339] using phylogenetic analyses in different gene segments. A recent study reported that next-generation sequencing can be useful in the influenza virus diagnosis and for the identification of the novel virulence markers and drug resistance [340].…”
Section: Discussionmentioning
confidence: 99%
“…Other techniques, such as gDNA depletion and host RNA depletion to enrich for viral RNA [13] and DNase pretreatment of the allantoic fluid to enrich for viral particles, have also been described [14]. Different methods have been employed for producing cDNA following enrichment, including sequence-independent single primer amplification (SISPA) and universal primers which have been used for sequencing RNA viruses [4, 15] including Newcastle disease virus (NDV) [11] and avian paramyxovirus (APMV) 4 and 6 [16]. …”
Section: Introductionmentioning
confidence: 99%